Small business organisations in Singapore - Tang, Shiuh Huei (2014)
Businesses in Singapore are encouraged to think big, to consider expansion and regionalisation. However, we must not forget about small businesses, not least because many businesses begin that way. One question is whether there are too many obstacles in the way of the small business, for example, the forms available to them in which to carry on business. Is there, or should there be a form under which a small business can operate more comfortably than present?